1998
DOI: 10.1089/lap.1998.8.209
|View full text |Cite
|
Sign up to set email alerts
|

Interval Appendectomy for Perforated Appendicitis in Children

Abstract: To determine the efficacy, safety, and cost of managing perforated appendicitis with intravenous antibiotics followed by an interval appendectomy, the charts of 87 children with ruptured appendicitis were retrospectively reviewed. These patients were treated with intravenous fluid resuscitation and antibiotics (consisting of clindamycin and ceftazidime) and underwent appendectomy, either on that admission (n = 46) or as a delayed interval procedure (n = 41). Antibiotics in all cases were discontinued either at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 3 publications
3
57
1
Order By: Relevance
“…There are current data with much larger populations of patients promote operating on these children with shorter hospitalizations and equivalent complications to the conservative group. However, there are also several studies reporting of conservative treatment (with or without interval appendectomy) as an option to appendectomy, with similar results [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 79%
“…There are current data with much larger populations of patients promote operating on these children with shorter hospitalizations and equivalent complications to the conservative group. However, there are also several studies reporting of conservative treatment (with or without interval appendectomy) as an option to appendectomy, with similar results [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 79%
“…7,8 Accurate preoperative diagnosis of acute non-perforated appendicitis using clinical examination and various radiological and biochemical tests is the main prerequisite for safe delayed appendicectomy.…”
Section: Discussionmentioning
confidence: 99%
“…30 Svensson et al recently reviewed the non-operative treatment of acute appendicitis in adults and children. 31 Ten retrospective studies [32][33][34][35][36][37][38][39][40][41] showed that an estimated 80% of patients with perforated appendicitis could be treated non-operatively. Such an approach must be viewed with caution given that Fitz urged early surgery for perforated disease.…”
Section: Mortality Through the 20th Centurymentioning
confidence: 99%